Arginine Methyltransferase PRMT7 Deregulates Expression of RUNX1 Target Genes in T-Cell Acute Lymphoblastic Leukemia - Oksa Laura; Mäkinen Artturi; Nikkilä Atte; Hyvärinen Noora; Laukkanen Saara; Rokka Anne; Haapaniemi Pekka; Seki Masafumi; Takita Junko; Kauko Otto; Heinäniemi Merja; Lohi Olli (MDPI, 2022)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy with no well-established prognostic biomarkers. We examined the expression of protein arginine methyltransferases across hematological malignancies and discovered high levels of PRMT7 mRNA in T-ALL, particularly in the mature subtypes of T-ALL. The genetic deletion of PRMT7 by CRISPR-Cas9 reduced the colony formation of T-ALL cells and changed arginine monomethylation patterns in protein complexes associated with the RNA and DNA processing and the T-ALL pathogenesis. Among them was RUNX1, whose target gene expression was consequently deregulated. These results suggest that PRMT7 plays an active role in the pathogenesis of T-ALL.